1984
DOI: 10.1113/jphysiol.1984.sp015118
|View full text |Cite
|
Sign up to set email alerts
|

Active sodium transport and fluid secretion in the gall‐bladder epithelium of Necturus.

Abstract: SUMMARY1. Intracellular Na, K and Cl activities (ac8, ac and ac1) and membrane potentials were measured in Necturus gall-bladder epithelium using double-barrelled ion-sensitive micro-electrodes. Mucosal membrane potential was about -55 mV and the mean control activities were aca = 14-7 mm, ac = 91-6 mm and ac1 = 20-3 mM.2. Replacing mucosal Na by K caused a fall in aca that followed an exponential time course. The rate of change in aea was linearly related to aca above a certain value (-3 mm). ac and ac, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…This means that the K+-selective micro-electrodes have a selectivity for K+ over Na+ of (40-7 1):1 (cf. Giraldez, 1984). g2+ interference on K+-selective micro-electrode response is negligible in the concentration range in which this divalent cation has been reported in the myoplasm (0-5-6 mM).…”
Section: Methodsmentioning
confidence: 94%
“…This means that the K+-selective micro-electrodes have a selectivity for K+ over Na+ of (40-7 1):1 (cf. Giraldez, 1984). g2+ interference on K+-selective micro-electrode response is negligible in the concentration range in which this divalent cation has been reported in the myoplasm (0-5-6 mM).…”
Section: Methodsmentioning
confidence: 94%
“…Giraldez (1984) found that aNai + fell and aKi + and aCli + increased, and from these changes he calculated (from Eq. 2 above) that cell volume should increase.…”
Section: Isosmotic Luminal Ion Replacements In Unstimulated Tissuesmentioning
confidence: 99%
“…If transapical membrane CI-influx is electroneutral because it is by cotransport with one or more cations (rather than by anion exchange), the change in cell volume during the reduction in luminal solution [C1-] can be estimated from the fall in aCl~-according to the following equation (Giraldez, 1984;Alvarez-Leefmans et al, 1988):…”
Section: Isosmotic Luminal Ion Replacements In Unstimulated Tissuesmentioning
confidence: 99%
“…cytoplasmic ion concentrations by Giraldez (1984), multiplied by our values for cell volume. These values agree well with other published data.…”
Section: Steady-state Ion Fluxes In Nectur Usmentioning
confidence: 99%
“…The results indicate that the activity in the corium during loading is small i compared to that in the mucosal bath and therefore the assumption underlying the method, that any cells loading in the corium at this activity will make a small contribution to the efflux and can reasonably be ignored, is correct. Giraldez (1984).…”
mentioning
confidence: 99%